2015
DOI: 10.1016/j.stemcr.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 Regulates the Acquisition of Gliogenic Competence by Neural Stem Cells

Abstract: SummaryMammalian neural stem/progenitor cells (NSPCs) sequentially generate neurons and glia during CNS development. Here we identified miRNA-153 (miR-153) as a modulator of the temporal regulation of NSPC differentiation. Overexpression (OE) of miR-153 delayed the onset of astrogliogenesis and maintained NSPCs in an undifferentiated state in vitro and in the developing cortex. The transcription factors nuclear factor I (NFI) A and B, essential regulators of the initiation of gliogenesis, were found to be targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…In this study, the neuronal differentiation was unaffected by the ischemic environment. Ischemia promotes interleukin‐6 (IL‐6) expression in the ipsilesional hemisphere (Gertz et al, ), and IL‐6–related protein is known as a strong inducer of gliogenesis in NSCs (Tsuyama et al, ). However, despite being attracted by and migrating toward the ischemic border, none of the cells in our grafts differentiated into astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the neuronal differentiation was unaffected by the ischemic environment. Ischemia promotes interleukin‐6 (IL‐6) expression in the ipsilesional hemisphere (Gertz et al, ), and IL‐6–related protein is known as a strong inducer of gliogenesis in NSCs (Tsuyama et al, ). However, despite being attracted by and migrating toward the ischemic border, none of the cells in our grafts differentiated into astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…miR-17 and its paralog miR-106 are able to prevent this switch during early development (Naka-Kaneda et al, 2014), and gliogenic factors are only expressed when the expression of these miRNAs gradually decreases during development, and this is then followed by the acquisition of gliogenic competence and glial differentiation (Naka-Kaneda et al, 2014). Furthermore, miR-153, which is highly expressed during early embryonic development, suppresses gliogenesisinducing factors [nuclear factor I (NFI) A and B] and prevents gliogenesis (Tsuyama et al, 2015). Once miR-153 levels are decreased, NFIA/B accumulates and NPCs acquire gliogenic competence (Tsuyama et al, 2015).…”
Section: Gliogenesismentioning
confidence: 99%
“…Furthermore, miR-153, which is highly expressed during early embryonic development, suppresses gliogenesisinducing factors [nuclear factor I (NFI) A and B] and prevents gliogenesis (Tsuyama et al, 2015). Once miR-153 levels are decreased, NFIA/B accumulates and NPCs acquire gliogenic competence (Tsuyama et al, 2015). Additional miRNAs that are important in glial cell lineage decisions include let-7 family members (Gökbuget et al, 2015;Patterson et al, 2014;Shenoy et al, 2015).…”
Section: Gliogenesismentioning
confidence: 99%
“…Another study demonstrated that activation of NF κ B signaling directly enhanced the transcription of NFIA in glioblastoma cells . The expression of NFIB was also regulated by microRNAs, such as miR‐372/373 , miR‐153 , miR‐365 , and miR‐124 . In adult neural progenitors, the Pax6–BAF complex transcriptionally upregulated NFIB .…”
Section: Discussionmentioning
confidence: 99%